Foundational Sight Singing - Stewart, Tobin (Open textbook library., 2022)
Sight reading music can be a daunting endeavor for aspiring, and even experienced, musicians. Foundational Sight Singing was created to provide a systematic approach to learn to read, hear and perform music. The ordered presentation of both melodies and rhythms in this text helps students develop accuracy and fluency in sight singing which is a fundamental skill for all musicians. It is a text for developing proficiency in reading and sight singing that can be used in a variety of contexts from individual practice to choral or instrumental ensemble rehearsals to college ear training courses. Multiple exercises are provided for drilling and practice at each level throughout the text to grow the students’ fluency and proficiency in reading and performing pitch and rhythm. This text will help students build a solid foundation upon which they can establish mastery.